How coaches use strongman implements in strength and conditioning practice - Winwood, P.; Cronin, J.; Keogh, J.; Dudson, M.; Gill, N. (International Journal of Sports Science and Coaching, 2014)
This article describes how strongman implements, which we defined as "any non-traditional implement integrated into strength and conditioning practice" are currently utilised by coaches to enhance athletic performance. Coaches (mean ±SD 34.0 ±8.2 y old, 9.8 ±6.7 y general strength and conditioning coaching experience) completed a self-reported 4-page survey. The subject group included coaches of amateur (n = 74), semi-professional (n = 38) and professional (n = 108) athletes. Eighty-eight percent (n = 193) of coaches reported using strongman implements in the training of their athletes. Coaches ranked sleds, ropes, kettlebells, tyres, sandbags and farmers walk bars as the top six implements used, and anaerobic/metabolic conditioning, explosive strength/power and muscle endurance as the three main physiological reasons for its use. The strongman implements were typically used in combination with traditional exercises in a gymnasium-based setting. Future research needs to evaluate the performance benefits of such training practices in controlled studies.